Herding, rent-seeking taxpayers, and endemic corruption - Gil S. Epstein; Ira N. Gang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In an environment with extensive corruption where much of the population evades paying their full taxes due, we tackle the question of optimal taxation when constituencies with opposing objectives (the poor and the rich) push tax policy in different directions. We think in terms of a government policy-maker, here called the tax administrator (TA), and rent-seeking lobbying efforts by poor and rich constituencies. We recognize taxpayers' inter-dependency as reflected in increased evasion likelihood when others are thought to be evading. Thus, our modelling incorporates elements from the theory of information cascades (herding) into a standard model of tax evasion. The poor and rich undergo a rent-seeking contest seeking to influence the TA in setting policy so that their constituency is favoured. The TA maximizes an objective function that is a weighted average of expected social welfare, their own interests, and investment in better tax administration.
Keywords: D72; G38; H26; O12; 330; tax evasion; corruption; herd behaviour; rent seeking; tax administration; poor